EDUKASI KARAKTER YANG INOVATIF (Studi Tentang Kepribadian Muslim yang Toleran) - Arif, Mohammad (PERMANA, 2015)
Education is an organization of the most fundamental in determining the life and future of a nation . Thus, in the process should be able to adjust to the conditions of the times. Education is very important to create a society berpedaban . Civilization of a nation will be added and the birth of an education system that is used by the nation. A civilized society , are educated people .According to Muhammad Naqib Al - Attas , Islamic education was more appropriately termed at- tadib ( compared tarbiyah term , study groups and other) because the concept of education tadib give adab / culture . Education takes place with a focus on the human being as subject and object , in order to meet the intellectual and spiritual potential . Along with rapid technological progress , automatically requires innovation in the field of education.Education is no longer enough organized traditionally , it flow without a clear target , and the absence of procedures for reaching a target that proved to be effective and efficient . If we retain the traditional ways without convening innovation , then obviously the Muslims and Islamic education will fall further behind in all aspects . For this reason the need for innovation in Islamic education is meant to be born Islamic education quality and competitive. Educational / character education is " an attempt to educate children to make decisions wisely and practice it in our daily lives , so that they can contribute to the environment " .Educational / character education is " a process of transformation of the values of life to be cultivated in a persons personality to become one in the behavior of the persons life " . Which contains three important key points , namely : a) the process of transformation of values , b ) cultivated in personality , and c ) become one in behavior.Characters in the school setting is " learning that led to the strengthening and development of the childs behavior ( students ) in their entirety based on a certain value referred to the school " . There are three important variables , namely : a ) the integrity of the character values in all subjects , b ) the spirit of development and strengthening of the behavior of learners , c ) the planting of the value derived from Pancasila and the 1945 Constitution , religious values , and norms in societyThe social function of religion is to support and preserve the existing community , both the unity and social solidarity . Religious social conditions can be seen in the activities of the students in pesantren salaf . The students in the study of religion and science uniquely pesantren always link between learning the value of obedience to the clerics and the value of devotion to God . Two elements ( learning and values obedience, piety) is a symbiotic mutualism . Value transendetal so closely in the life of students in pesantren salaf .Islam asserts that the human ego is free and therefore his actions can be assessed by reference to the rules of morality . Religion acts strengthen the unity and stability of the society by supporting social control, sustain the values and goals are established , and provides a means to resolve the error and alienation . Religion can also perform the role of the treatise and proved himself to be something that was not resolved or even a subversive influence of orchestrating the particular societyCultural strategy is designed for the development of mature personality for the people of Islam by broadening their horizons , widen the scope of their commitments, deepen their awareness of the complexity of the environment of mankind , and strengthen their solidarity with fellow human beings regardless of their political ideology , origins ethnicity , cultural background , and religious beliefs. In order for this goal can be achieved will require a full development of rational behavior of Muslims towards life. Commitment togetherness in maintaining harmony in diversity is needed . Peace will not be achieved without mutual respect and uphold a sense of togetherness in society . So it will be able to produce the tolerant Muslims , the bond of national unity in the NKRI.Keywords : Character, Education, Innovative.